2018
DOI: 10.1139/apnm-2017-0304
|View full text |Cite
|
Sign up to set email alerts
|

Participation in moderate-to-vigorous leisure time physical activity is related to decreased visceral adipose tissue in adults with spinal cord injury

Abstract: Increased visceral adiposity places individuals with chronic spinal cord injury (SCI) at increased risk of cardiometabolic disease. The purpose of this study was to identify if people with chronic SCI who participate in any moderate- to vigorous-intensity leisure time physical activity (LTPA) have lower visceral adipose tissue (VAT) area compared with those who report none. Participants included 136 adult men (n = 100) and women (n = 36) with chronic (mean (±SD) 15.6 ± 11.3 years post-injury) tetraplegia (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our results are again supported by previous findings [12]. In addition, a recent study by Pelletier et al [27] (n = 136, mean age 49 years, mean time since injury 16 years, 74% men) showed a significant relationship between less visceral adipose tissue and moderate-to-heavy LTPA. Together, these findings infer that participation in LTPA has a promising effect on body composition, although causal inferences cannot be made due to the cross-sectional study designs.…”
Section: Body Mass Index and Waist Circumferencesupporting
confidence: 93%
“…Our results are again supported by previous findings [12]. In addition, a recent study by Pelletier et al [27] (n = 136, mean age 49 years, mean time since injury 16 years, 74% men) showed a significant relationship between less visceral adipose tissue and moderate-to-heavy LTPA. Together, these findings infer that participation in LTPA has a promising effect on body composition, although causal inferences cannot be made due to the cross-sectional study designs.…”
Section: Body Mass Index and Waist Circumferencesupporting
confidence: 93%
“…Regular moderate-to-vigorous physical activity is associated with less visceral adipose tissue in persons with SCI. 44 Additionally, endurance training has been shown to improve body composition in this population. 45,46 While many studies performed in nondisabled individuals have shown improved body composition following HIIT in both men and women, [47][48][49] we are aware of only one study that assessed body composition following HIIT in the SCI population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that VAT is associated with a spectrum of inflammatory biomarkers and likely impacts hepatic metabolism and causes mitochondrial dysfunction (Farkas et al, 2017; O'Brien, Wade, et al, 2017; Sumrell et al, 2018). The increase in the level of physical activity and NMES‐RT successfully reduce VAT in persons with SCI (Gorgey, Khalil, et al, 2019; Pelletier et al, 2018). During the initial 16‐week training period in these participants, both TT+RT and TT only modestly decreased VAT CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Alternating leg exercise with an arm cycling exercise or circuit RT programs may encourage long‐term compliance and allow participants to increase their daily level of physical activity. Leisure time physical activity has been shown to attenuate the development of chronic comorbidities and the gain in VAT in persons with SCI (Buchholz et al, 2009; Pelletier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%